Tata Tertib Sekolah dan Kedisiplinan Belajar di MA Yayasan Pendidikan Kalangsari Cijulang - Sari, Rini Indah (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2023)
This study aims to find out how to implement school rules at MA YPK Cijulang and also the principal as a manager in an educational institution must have three main intelligences, namely professional intelligence, personal intelligence, and managerial intelligence so that he can cooperate with others. With this ability the principal is able to improve school performance through discipline coaching, namely compiling and implementing school rules. The problems faced by MA YPK Cijulang are the lack of a sense of responsibility for the tasks they carry out, the lack of adherence to school rules that are applied by the school. The purpose of this study was to find out how the principal's management applied school rules and regulations, to find out the role of the school principal in implementing school rules, and to find out the principal's obstacles in implementing school rules. This research is qualitative in nature, with the background taken at MA YPK Cijulang. Data collection methods are carried out by conducting observations, interviews, and documentation. Data analysis was carried out by collecting all data then analyzing data, presenting data and drawing conclusions. The results of the study show that school rules cannot control all student behavior at MA YPK Cijulang, but school rules are sufficient to raise awareness and provide a deterrent effect to students who have committed violations. So it can be said that school rules are good enough to be used as a tool to control student behavior.